Cervical disc width index is a reliable parameter and consistent in young growing Dutch Warmblood horses. Issue 1 (13th October 2020) - Veraa, Stefanie; Scheffer, Carmen J.W.; Smeets, Danielle H.M.; de Bruin, Renske B.; Hoogendoorn, Arie C.; Vernooij, Johannes C.M.; Nielen, Mirjam; Back, Willem
Abstract: Intervertebral disc disease, as well as the associated alteration of the radiographic intervertebral disc space width, has been reported in horses. Disc height index (DHI) has proven to be an accurate and objective parameter in other species but data related to this parameter are lacking in horses. Therefore, the aims of this retrospective longitudinal diagnostic accuracy study were (a) to evaluate the reliability of measurements within and between observers of the equine Disc Width Index (EDWI) as a parameter for radiographic equine cervical intervertebral disc space width, and (b) to evaluate the sequential development of the EDWI over time. For this, EDWI from all intervertebral disc spaces between second cervical (C) to first thoracic (Th) vertebrae were obtained in a group of 39 Dutch Warmblood horses at 1, 5, and 18 months of age, by one European College of Veterinary Diagnostic Imaging (ECVDI) board‐certified veterinary radiologist (S.V.) and two veterinary students. Bland‐Altmann plots and intraclass Correlation Coefficient revealed a good intra‐ and interobserver agreement. A linear mixed‐effect model did reveal that mean EDWI increases significantly toward the caudal cervical spine, but did not differ significantly for a certain location over time or between sexes. Spearman's rank test did show a significant correlation between the vertebral alignment angle induced by different head‐neck positions and a normalized EDWI ( ρ = 0.33, P < .0001). Student's t ‐test revealed that the presence of C6‐C7 transposition of the transverse processes did not influence EDWI significantly. It was concluded that EDWI represents a reliable parameter for equine cervical radiographic intervertebral disc space width. Practical implementation of EDWI warrants monitoring in a group of adult horses while maintaining a standardized head‐neck position.